Design and validation of a clinical whole genome sequencing-based assay for patient screening in a large healthcare system - Wagner, Josiah T.; Welle, John T.; Lucas Beckett, Isabelle A.; Emery, Kate R.; Cosgrove, Benjamin A.; Olszewski, Krzysztof; Wagner, Nick; Bower, Tucker C.; Yuan, Li Chi; Shull, Eric M.; Jade, Kathleen; Clemens, Jon; et al. (Frontiers in Molecular Biosciences, 2025)
IntroductionPopulation genetic screening is rapidly emerging as a key methodology in the clinical laboratory for detecting actionable genomic conditions in asymptomatic patients. While current clinical methods are largely focused on targeted gene panels, the increasing efficiency of next-generation sequencing (NGS) platforms permits the use of whole genome sequencing (WGS) for routine clinical applications. The key advantage of WGS is that the complete genome produced by a single sequencing event can form the basis for a patient’s genomic health care record for reanalysis throughout a patient’s lifetime.MethodsWe developed a scalable clinical WGS-based lab developed procedure (LDP) for heritable disease gene testing and pharmacogenomics (PGx). We performed extensive validation across a range of blood, saliva, and reference specimens.ResultsThe clinical deliverable for the WGS LDP was 78 genes associated with actionable genomic conditions and 4 PGx genes. The validation cohort consisted of samples from 188 study participants that were orthogonally sequenced at commercial reference laboratories and additional reference materials. The WGS LDP demonstrated excellent sensitivity, specificity, and accuracy.ConclusionThe deployed LDP was then used to sequence over 2,000 patients as part of a broader clinical implementation study (“Geno4ME”). Our findings support WGS as a viable method for broad clinical screening.